Impact of rapid urban growth on sustainability of soil and water resources in Jordan - Higgitt D.L. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
The Hashemite Kingdom of Jordan provides an example of a nation state in the eastern Mediterranean, which has undergone profound changes in population--environment dynamics during the twentieth century. The structure of interdependency between urbanisation and agriculture is distinctively shaped by the political history of the region. The development of nationhood imposed both restrictions to the traditional mobility of pastoralists and the need for national identity. Environmental change driven by political and economic context has been rapid and varied. The growing demand for the use of water resources in particular from rapidly expanding urban centres is problematic for sustainable development. The structure between urbanisation and agricultural production is encroached by issues of population growth, migration, concepts of territory and boundaries, land tenure and factors driving mobility and settlement. The rapid growth of a low density city has not only changed the balance of urban-rural population but has consumed land which is capable of sustaining rainfed agriculture, which is a rare commodity in Jordan. Water demand has increased with population abd has required groundwater to be exploited and pumped to Amman.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)